Ekstraksi DNA Nibung (Oncosperma tigillarium (Jack) Ridl.) Menggunakan Beberapa Jenis Buffer Terhadap Kualitas Genomik DNA - Mahadi, Imam; Sayuti, Irda; Nursal, Nursal (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
The Nibung (Oncosperma tigillarium (Jack) Ridl.) is a plant that serves as the floral mascot of Riau and symbolizes the spirit of unity and brotherhood among its people. Genetic diversity research is essential for the conservation of this species, with DNA extraction being a critical initial step. This study compared three types of buffers: CTAB, Alkyl Benzene Sulfonate (ABS) surfactant detergent, and Sodium Laureth Sulfate (SLS) surfactant detergent. The aim of this research was to identify alternative buffers to replace CTAB and simplify the extraction of genomic DNA from Nibung. Parameters measured included the presence of DNA and DNA concentration, using electrophoresis and a nanodrop spectrophotometer. The results showed that clear genomic DNA bands were successfully obtained for 24 Nibung accessions, with only two accessions, Nibung2s and Nibung6s, showing smeared bands when using the SLS surfactant detergent buffer. The genomic DNA concentrations ranged from 526.2 to 3,829.2 ng/µl. These concentrations are suitable for use as DNA templates in further research. Thus, both ABS and SLS surfactant detergent buffers can be considered viable alternatives to CTAB for extracting genomic DNA from Nibung. Key words: Buffer; DNA bands; DNA extraction; DNA Concentration; Extraction optimization.